The supply risk analysis process in small and medium-sized enterprises = Proces analizy ryzyka zaopatrzenia w małych i średnich przedsiębiorstwach - Kozaryn, Maciej; Wasilewski, Wiesław (Zielona Góra: Faculty of Economics and Management Press)
The identification and evaluation of risk, especially in small and medium enterprises - has been a topic of examination by scientists from the very beginning. Expenditure connected with the implementation and proper execution of risk measurement methods is also of prominent importance. Every organization must face risk during its operation. Quick identification and effective evaluation of its level makes it possible to maintain fluidity of activities on the market at a constant level.
Keywords: ryzyko; analiza ryzyka; identyfikacja ryzyka; ocena ryzyka; risk; risk analysis; risk identification; risk assessment